Setting up cloud based shared ARMv8 machine for Computer Architecture Education - Asretdinova, Lobar; Asretdinova, Muhabbat (MMIT Proceedings, 2025)
In the context of rapid technological advancement, it is essential to prepare students to work with modern processor architectures. This paper presents the integration of practical ARMv8 learning into a computer architecture course using the Orange Pi 5 Plus single-board computer and virtual Linux environments, where students performed tasks involving ARMv8 assembly programming, debugging with GDB, system calls, and memory management. The results demonstrate increased student confidence and a deeper understanding of theoretical concepts, highlighting the significance of hands-on learning and the use of virtualization in technical education.